Opportunistic Quantitative CT Bone Mineral Density Measurement at the Proximal Femur Using Routine Contrast‐Enhanced Scans: Direct Comparison With DXA in 355 Adults. (6th May 2016) - Ziemlewicz, Timothy J; Maciejewski, Alyssa; Binkley, Neil; Brett, Alan D; Brown, J Keenan; Pickhardt, Perry J
ABSTRACT: For patients undergoing routine contrast‐enhanced CT examinations, an opportunity exists for concurrent osteoporosis screening without additional radiation exposure or patient time using proximal femur CT X‐ray absorptiometry (CTXA). We investigated the effect of i.v. contrast enhancement on femoral neck CTXA T ‐score measurement compared with DXA. This cohort included 355 adults (277 female; mean age, 59.7 ± 13.3 years; range, 21 to 90 years) who underwent standard contrast‐enhanced CT assessment at 120 kVp over an 8‐year interval, as well as DXA BMD assessment within 100 days of the CT study (mean 46 ± 30 days). Linear regression and a Bland‐Altman plot were performed to compare DXA and CTXA results. CTXA diagnostic sensitivity and specificity was evaluated with DXA as the reference standard. There was good correlation between DXA and CTXA ( r 2  = 0.824 for both areal BMD and T ‐scores) and the SD of the distribution of residuals was 0.063 g/cm 2 or 0.45 T ‐score units. There was no trend in differences between the two measurements and a small bias was noted with DXA T ‐score +0.18 units higher than CTXA. CTXA had a sensitivity for discriminating normal from low bone mineral density of 94.9% (95% CI, 90.6% to 97.4%). For opportunistic osteoporosis screening at routine post‐contrast abdominopelvic CT scans, CTXA produces T ‐scores similar to DXA. Because femoral neck CTXA BMD measurement is now included in the WHO Fracture Risk Assessment Tool (FRAX) tool, this opportunistic method could help to increase osteoporosis screening because it can be applied regardless of the clinical indication for CT scanning. © 2016 American Society for Bone and Mineral Research.